Qualidade fisiológica e armazenamento de sementes de ipê-verde (Cybistax antisyphilitica (Mart.) Mart.) - Melo, Paulo Régis Bandeira de [UNESP] (2009)
Cybistax antisyphilitica (Mart.) Mart. is a Brazilian native tree species, with medicinal properties, belonging family Bignoniaceae and often found in Cerrado biome. Can be used in project with objective for heterogeneous florestation directed to the recomposition of degraded areas, permanent preservation area or ornamental purposes. This study was carried out to evaluate conditions to the germination standard test, verify the possibility the use the electrical conductivity and accelerated aging tests to studied the physiological quality of seeds, as well as to evaluate the storage of seed lots in order to helpful in quality programs and consequent decision in relation to possible sow, discard, sale, donation, storage, among others. This seeds lots were from Araraquara (SP), Assis (SP) and Guariba (SP), district. For the processing of seeds was removed manually adnated wing and subsequent homogenize in soil compartment, separately for each lot. In the germination test were evaluated seven temperatures (20 oC, 25 oC, 30 oC, 35 oC, 20-30 oC, 20-35 oC and 25-35 oC) and four substrates (sand, germitest paper, blotting-paper and vermiculite), for two lots of seeds. For vigor tests, were evaluated the possibility to adapt and use of electrical conductivity, conducted at 25 oC in samples of 50, 75 and 100 seeds, soaking in 75 and 100 mL of distilled water for different periods (2, 4, 6, 12, 24, 48 and 72 h) and traditional test of accelerated aging (without NaCl) and saline solution (with NaCl), at 45 0C at different times (24, 48, 72 and 96 h), to four seed lots. For evaluate the behaviour in storage, two seed lots were storage in paper kraft bag and kept in room temperature (24 oC ± 2 oC and RH 53% ± 3%); storage in paper kraft bag inside of the wood fiber pots at climated room (22 oC ± 2 oC and RH 56% ± 15%) and storage in plastic bag in cold chamber (9 oC ± 2 oC and RH 43% ± 5%)... (Complete abstract click electronic access below)